Topological Phonon Modes in a Two-Dimensional Wigner Crystal - Ji, Wen-Cheng; Jun-Ren Shi (Chinese Phys. Lett., 2017)
We investigate the spin–orbit coupling effect in a two-dimensional (2D) Wigner crystal. It is shown that sufficiently strong spin–orbit coupling and an appropriate sign of g-factor could transform the Wigner crystal to a topological phonon system. We demonstrate the existence of chiral phonon edge modes in finite size samples, as well as the robustness of the modes in the topological phase. We explore the possibility of realizing the topological phonon system in 2D Wigner crystals confined in semiconductor quantum wells/heterostructure. It is found that the spin–orbit coupling is too weak for driving a topological phase transition in these systems. It is argued that one may look for topological phonon systems in correlated Wigner crystals with emergent effective spin–orbit coupling.